Analysis of Generation Z Students' Interest in Agricultural Careers Using the Social Cognitive Career Theory - Melani, April; Karim, Akhmad Rizqul; Prasetyo, Kunandar (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
The declining interest of the younger generation, particularly Generation Z, in pursuing careers in the agricultural sector has emerged as a critical concern requiring comprehensive analysis. This study investigates the career interests of agricultural students through the lens of the Social Cognitive Career Theory (SCCT), which highlights the influence of self-efficacy, outcome expectations, and personal career goals in shaping career aspirations. Employing a quantitative research design, data were collected from 338 students enrolled at Jenderal Soedirman University (UNSOED), Muhammadiyah University of Purwokerto (UMP), and Nahdlatul Ulama University (UNU) Purwokerto using a quota sampling method. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that students’ interest in agricultural careers is at a moderate level. Outcome expectations significantly and positively influence both career interest and goals. Although self-efficacy does not directly affect career interest, it exerts an indirect influence through its impact on career goals. These results underscore the importance of enhancing students’ career goals and positive expectations to foster greater interest in agricultural careers.